Body Weight and Blood Biochemical Changes Following Nutritional Supplementation in Prepubertal Jaffrabadi Buffalo (Bubalus bubalis) Heifers - Raval, RJ; Vala, KB; Kalariya, VK; Dhami, AJ; Kavani, FS (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The high plan of nutrition right from an early age is believed to enhance ovarian activity and early onset of puberty in heifers. This studywas therefore conducted to know the body weight, ovarian and blood biochemical changes in nutritionally supplemented and controlgroups of prepubertal Jaffrabadi buffalo (Bubalus bubalis) heifers. A total of 12 animals of 30 ± 2 month's age and the identical bodyweight of 380–410 kg from Cattle Breeding Farm, JAU, Junagadh were utilized for this study. They were randomly divided into two equalgroups of 6 animals in each treatment and control groups. The heifers of the treatment group were supplemented with bypass fat (100g), bypass protein (950 g) and chelated mineral mixture (50 g) over the routine farm feeding practices of control group, and its effecton body weight gain and blood biochemical profiles were studied at a monthly interval during 6 months of experimental period. Theoverall effect of nutritional supplementation on animals body weight, blood glucose and total cholesterol over the control group wasstatistically non-significant (p >0.05) yet beneficial. The plasma total protein levels in the supplemented group increased with a durationof supplement and levels were significantly (p 4 mm in diameters (5.00 ± 0.13to 6.67 ± 0.40), without significant variation in diameters of largest follicles (9.14 ± 0.45 to 10.27 ± 0.85 mm) between groups or periods.However, none of the heifers exhibited behavioral signs of estrus during 6 months study, in spite of the establishment of cyclicity withthe presence of developed follicles, or CLs suggesting silent ovulation, at 36 ± 2 months of age in this breed.
Keywords: Body weight; Blood glucose; Nutrients supplementation; Prepubertal Jaffrabadi heifers; otal cholesterol,; Total protein